Prevalence of a set of risk factors for chronic diseases in the city of São Paulo, Brazil - Marcopito, Luiz Francisco; Rodrigues, Sérgio São Fins; Pacheco, Maria Aparecida; Shirassu, Mírian Matsura; Goldfeder, Artur Jaques; Moraes, Marco Antonio de (Revista de Saúde Pública, 2005)
OBJECTIVE: To estimate the prevalence of a set of risk factors for non-transmissible chronic diseases and compare it to that found 15-16 years ago in a similar survey. METHODS: A cross-sectional household survey was carried out comprising a random sample of people aged 15-59 years in the city of São Paulo between 2001 and 2002. The total of 2,103 people answered a questionnaire and had their blood pressure, weight, height, waist and hip circumferences measured. For a third of these participants, their total cholesterol, HDL-cholesterol, triglycerides and glucose levels were determined. RESULTS: The total age-adjusted prevalences in the study age group were as follows: smoking, 22.6%; uncontrolled blood pressure, 24.3%; obesity, 13.7%; increased waist circumference, 19.7%; total cholesterol ³240 mg/dL, 8.1%; HDL-cholesterol